Design and development of a QPSK modulator - Akter, Shanaz; Sharmin, Nusrat; Islam, Md. Iftekharul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.